Influence of the initial angular distribution on strong-field molecular dissociation - Yu, Youliang; Zeng, Shuo; Hernandez, J. V.; Wang, Yujun; Esry, Brett D. (My University, 2016)
We study few-cycle, strong-field dissociation of aligned H-2(+) by solving the time-dependent Schrodinger equation including rotation. We examine the dependence of the final angular distribution, the kinetic energy release spectrum, and the total dissociation yield on the initial nuclear angular distribution. In particular, we look at the dependence on the relative angle theta(0) between the laser polarization and the symmetry axis of a well-aligned initial distribution, as well as the dependence on the delay between the "pump" pulse that prepares the alignment and the few-cycle probe pulse. Surprisingly, we find the dissociation probability for theta(0) = 90 degrees can be appreciable even though the transitions involved are purely parallel. We therefore address the limits of the commonly held "ball-and-stick" picture for molecules in intense fields as well as the validity of the axial recoil approximation.
Citation: Yu, Y. L., Zeng, S., Hernandez, J. V., Wang, Y. J., & Esry, B. D. (2016). Influence of the initial angular distribution on strong-field molecular dissociation. Physical Review A, 94(2), 6. doi:10.1103/PhysRevA.94.023423
Keywords: Intense Laser Fields; Dynamics; Optics; Physics